KLASIFIKASI KARAKTERISTIK KEPRIBADIAN MAHASISWA UNIVERSITAS AMIKOM YOGYAKARTA DENGAN MENGGUNAKAN METODE NAIVE BAYES - Dimas Midyan Alam; Ahmad Tedi Dwi Prabowo; Anif Prabono; Mahendra Wishnu Pratama (Jendela Inovasi Daerah, 2020)
Students have an age which is a transition period from children to teenagers. Problems caused by this transition cause difficulties for students who are still unstable in controlling emotions. Problems that arise because of the personality of students who began to change the relationship around him. Required in education that is needed a system that can understand the personality type of students for the purchase of students in accordance with their personality types. This research involves collecting data using the Naïve Bayes method to determine class classification characteristics of students, namely sanguin, koleris, melancholy, or plegmatic classes. The attributes used in this study consisted of 7 attributes, namely gender, age, school, answers to test A, answers to test B, answers to tests C, and answers to tests D. The system testing was carried out three times with different training calculation data- different. The data used in the testing of this system is questionnaire data based on Hippocrates-Galenus Typology which is filled with 320 students. The data used is divided into 3 data data models with 100 data each and 20 data as test data. Based on the results of 7 students in the Sanguine class, 6 students of the koleris class, 3 students of the melancholy class, and 4 students of the plegmatic class with a total of 20 test data items.